Modified Stability of microRNA-Loaded Nanoparticles - Katja Fresacher-Scheiber; Ivana Ruseska; Henrik Siboni; Martin Reiser; Fabio Falsone; Leonhard Grill; Andreas Zimmer (MDPI AG, 2022)
microRNAs represent promising drugs to treat and prevent several diseases, such as diabetes mellitus. microRNA delivery brings many obstacles to overcome, and one strategy to bypass them is the manufacturing of self-assembled microRNA protein nanoparticles. In this work, a microRNA was combined with the cell-penetrating peptide protamine, forming so-called proticles. Previous studies demonstrated a lack of microRNA dissociation from proticles. Therefore, the goal of this study was to show the success of functionalizing binary proticles with citric acid in order to reduce the binding strength between the microRNA and protamine and further enable sufficient dissociation. Thus, we outline the importance of the present protons provided by the acid in influencing colloidal stability, achieving a constant particle size, and monodispersing the particle size distribution. The use of citric acid also provoked an increase in drug loading. Against all expectations, the AFM investigations demonstrated that our nanoparticles were loose complexes mainly consisting of water, and the addition of citric acid led to a change in shape. Moreover, a successful reduction in binding affinity and nanoparticulate stability are highlighted. Low cellular toxicity and a constant cellular uptake are demonstrated, and as uptake routes, active and passive pathways are discussed.